An investigation of the behavior of solvent based polycaprolactone ink for material jetting - He, Yinfeng; Wildman, Ricky D.; Tuck, Christopher; Christie, Steven D.R.; Edmonson, Steven (Nature Publishing Group, 2016)
An initial study of processing bioresorbable polycaprolactone (PCL) through material jetting was conducted using a Fujifilm Dimatix DMP-2830 material printer. The aim of this work was to investigate a potential solvent based method of jetting polycaprolactone. Several solvents were attempt to prepared PCL solvent based ink and 1, 4-dioxane was chosen with the consideration of both solubility and safety. The morphology of PCL formed under different substrate temperatures, droplet spacings were investigated. Multi-layer PCL structures were printed and characterized. This work shows that biodegradable polycaporlactone can be processed through material jetting by dissolving it.